Estabelecimentos isolados de ensino superior: um estudo das fundações educacionais de SC - Bordignon, Genuino (1978)
This work is based upon the analysis of the Isolated Institutions of Third Grade Teaching. The universe of the analysis are the Educational Foundations in Santa Catarina and their 3rd grade Teaching Units. Such Foundations, created by the State or City Government, made possible the interiorization and regionalization of the 3rd grade Teaching in Santa Catarina, and by the time this search was done, they gathered 2/3 of the whole student population of such a teaching level, there. The University is the norm and the isolated institutions are the exception under the Brazilian law for the Third Grade Teaching. Nevertheless, the exception has statistically a modal position. The university and the isolated institutions are separate realities and normally, found in different surroundings. No wonder, if both are different, refered one to another, their concept must be various also. The Isolated Institution is still searching for its institutional identity, its destination. In the search of the Isolated Institutions identity is considered the know-how Santa Catarina accumulated through its Educational Foundations. This study deals with those Institutions under three viewpoints: the aims of the Institutions, their structural organization and the ways they interact with the environment. The analysis of the aims has a triple dimension: the goals and functions of the 3rd Grade Teaching as refered to the law; the goals and functions of the Educational Foundations and their Teaching units, concerning to the various legal commands, and the results attained by such Institutions. As far as the analysis of the aimed purposes are concerned, as well as the results, three kinds of people are focused: the lnstitution’s teaching-administrative personnel, the students and the communities. Inferences are drawn between the aimed goals and the reached ones and the personal fulfillment of the teachers and administrators. Compared to what students and conununities alike expect from them in order to elevate the coherence between the aimed and the reached goals, and the discrepancy among the interested as far as the aims are concerned. An analysis is made aiming to output the lack of coherence between the formal structure and the administrative action of the Institutions. One believes that formal structures sophisticated beyond the needed complexity of the organization create 'formalities', here taken as discrepancy between the rule and the behavior. The 'formalities' justify the incoherence between the aimed and the attained, as far as goals are concerned. The data show that there are connections between the kind of structure (formal-concrete) and the union of aims and results. Siftings are made to explain the disruption of aiming among the partners concerning the interaction with the environment, here understood as the action of the Third Grade Teaching Institutions upon the social neighborhood and the performance of this one upon that one, as an 'exchange'. Here also is drawn an association between the Studied variables. The data here shown lead us to state that the Isolated Institutions of Third Grade Teaching are marching toward their own destiny. Alternative actions are proposed aiming to reach the Isolated Institutions' identity, besides the urge to deeper studies on this subject.